Diakónia az Újszövetségben - KÓKAI-NAGY, Viktor (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2019)
Diaconia in the New Testament. Our research yields the conclusion that the diaconia is a general term, meaning the preaching of the gospel by words and deeds. The fact that in the NT, this activity is labelled as diakonia, marks that this is not a kind of function, competency, or privilege. It is a ministry for God and for humans and go-between God and men, media-tor of divine message. This testifies to what God has done for us in Jesus. Both aspects of the practice of the diaconia are important (word and deed) for the ministry of salvation.